Efeitos de um programa de aconselhamento de atividade física para trabalhadores da atenção básica: um ensaio clínico randomizado - Bisetto, Leandro Augusto (2020)
Introduction: Although the benefits of physical activity (PA) are well-known, little is know about effects of PA interventions for health professionals of Primary Health Care. Aim: This study aims to analyze the effects of an intervention for behavior change on physical levels among primary health care workers in São Carlos, São Paulo state, Brazil. Methods: Participants (58) were randomized in: i) Intervention Group (IG) (n=29) or ii) Control Group (GC) (n=29). The intervention provided 40-minutes of counseling for behavior change in PA once a week for one month as well as daily motivational messages by phone. PA was measured using the International Physical Activity Questionnaire (IPAQ), long version. LifeStyle Profile Scale (PEVI) measured lifestyle levels. The groups answered the questionnaires at the end of the program (one month) and three months later (follow-up). Lifestyle and PA difference-means of the groups were compared by time (pre, post, and follow-up). As the estimated media for PEVI scores and AF minutes weekly between the baseline moments, powders and follow-up were compared using Generalized Estimation Equations. Results: A sample was made up of 100% women, with an average age of 46.8 (± 11.6) and 41.1 (± 7.0) for IG and CG, respectively. After an intervention and without a follow-up period, the IG increased more PA without leisure time when compared to the control group (p = 0.021). As variations in the general lifestyle, the detachment PA and total PA did not show statistically significant differences between the groups.Conclusion: The program was effective in increasing the level of PA.